Balloon Occlusion Therapy For Placenta Previa Bleeding:A Literature Review - Saifana, Qanita; Soraya Wijanarko , Rahma (Green Publisher Indonesia, 2023)
Placenta previa (PP) is a condition where the placenta abnormally implants in the lower uterine segment, with complete coverage of the internal cervical os termed as complete placenta previa (CPP). Often associated with placental adhesion and abnormal placentation, known as placenta accreta, it poses a risk of massive peripartum bleeding, increasing the likelihood of requiring blood transfusions, and contributing to maternal morbidity and mortality. PP cases currently affect 0.56% of women.The risk of hysterectomy post-cesarean delivery in PP is 3.5%, significantly higher than in mothers without PP. The surge in cesarean deliveries for PP substantially impacts gynecological medical care costs. PP has various risk factors, including maternal age, abortion history, uterine myoma, high body mass index, high baby weight, male fetus, maternal tobacco use, and a prior cesarean section. Placental adhesions, such as accreta, percreta, or increta, further complicate the condition, with a prevalence of 0.3-2% in the third trimester, often requiring blood transfusions. Surgical methods, like ligation of uterine arteries, floseal usage, uterine compression sutures, and hemostatic sutures, aim to restore placental homeostasis, with hysterectomy considered if bleeding persists. Balloon occlusion, employed since the 1980s, has shown promise in reducing bleeding during cesarean operations for PP by stopping blood flow to the targeted area, specifically the internal iliac artery. The procedure involves inflating a balloon with saline, compressing the artery wall to achieve hemostasis. Despite its potential benefits, balloon occlusion carries possible side effects and complications, including arterial injury, infection, uncontrolled bleeding, ischemia, and allergic reactions. Conservative therapy in PP includes close monitoring, bed rest, and blood transfusions if necessary, while surgical interventions like uterine artery embolization and hysterectomy are considered. However, surgical therapies present risks and potential impacts on future pregnancies. Balloon occlusion's application requires careful consideration of diagnosis accuracy, placental invasion degree assessment, and skilled medical personnel. The procedure's benefits and risks must be thoroughly evaluated, and patients should be informed comprehensively before consenting to the treatment. While studies suggest its effectiveness in reducing PP bleeding and minimizing complications, further research, particularly large-scale randomized controlled clinical trials, is essential to validate its widespread effectiveness, understand influencing variables, and assess its mechanism of action in-depth. Such research will contribute to refining balloon occlusion's usage for improved outcomes in PP cases.